Survival of bacillus cereus in artificially contaminated uht milk and infant milk - Kong, Wan Wei (Universiti Malaysia Sarawak (UNIMAS), 2015)
The inappropriate storage temperature and pH enable the survival of Bacillus cereus, a known food pathogen in processed milk products, resulting in foodborne diseases. In the present study, UHT milk and infant milk purchased from local supermarkets in Kuching, Sarawak were inoculated with 103 CFU/ml of B. cereus. Selected storage temperatures of4 'C-7 'C, 10 'C-13 'C, 25 'C, 35 'C, 45 'C and 55 'C were used to investigate the effects of temperature on the survival of B. cereus. Initial pH of 6.20,6.40, 6.60 and 6.80 at refrigerated temperature (4 'C-7 'C) were used to study the effects of pH on the survival of B. cereus. Enumeration of colony counts were investigated daily for the duration of seven days. Gram staining and Polymerase Chain Reaction (PCR) targeting gyrB gene were performed for the confirmation of B. cereus isolates. The present findings revealed that the survival of B. cereus in UHT milk and infant mil k showed significant differences (p<O.05) in different temperatures and pH. At 25 'C, there were significant difference (p<0.05) between the survival of B. cereus in UHT milk and infant milk. B. cereus were able to survive under all the experimental temperatures. However, growth was detected at all storage temperatures except 55 'c. Survival of B. cereus in artificially contaminated UHT milk and infant milk with different initial pH stored at referigerated temperature were also recorded. The results from this study can be treated as background data for the implementation ofsafety measure to avoid food poisoning caused by B. cereliS.